Clinical treatment strategies and perioperative management of restenosis or secondary deep venous thrombosis after iliac vein balloon angioplasty - Zi-shuo Yang; Shuang-jie Tang (Phlebology: The Journal of Venous Disease, 2026)
Objective To explore the surgical selection of iliac vein balloon angioplasty, as well as the treatment and management of postoperative complications including restenosis and secondary deep venous thrombosis. Methods All 55 enrolled patients received routine telephone follow-up, and imaging reexamination and statistical analysis were only performed on 10 patients complicated with restenosis or secondary thrombosis after balloon angioplasty. Conclusion This study provides reference basis for the selection of clinical surgical schemes and perioperative management of iliac vein balloon angioplasty in the treatment of iliac vein compression syndrome.